Front Cover: Addressing the Reproducibility of Photocatalytic Carbon Dioxide Reduction (ChemCatChem 6/2020). Issue 6 (4th February 2020) - Marx, Maximilian; Mele, Andrea; Spannenberg, Anke; Steinlechner, Christoph; Junge, Henrik; Schollhammer, Philippe; Beller, Matthias
Abstract : The Front Cover shows mountain scenery on top of which the conversion of CO2 and water into CO, HCO2 H and H2 mediated by light is depicted. Variable heights of the highlighted spots on the yellow mountain ridge (TON ridge) symbolize the fluctuant turnover numbers of a poorly reproducible catalytic reaction. In their Full Paper, M. Marx et al. outline problems with the reproducibility of photocatalytic transformations, specifically carbon dioxide reduction. Utilizing Fe hydrogenase mimics in combination with a Cu photosensitizer they highlight that complex equilibria and general problems associated with photocatalysis reaction set‐up can result in low reproducibility. Based on their results, suggestions are made on how to achieve higher reproducibility in such catalyst development. This main objective is also highlighted on the central signpost in the cover picture. More information can be found in the Full Paper by M. Marx et al. on page 1603 in Issue 6, 2020 (DOI: 10.1002/cctc.201901686 ).